PERANCANGAN MESIN PEMBUAT BATAKO STYROFOAM UNTUK PENGUSAHA KECIL - Halim, Abdul; Restu, Arie; Pitrandjalisari, Vitri (WIDYA TEKNIKA, 2014)
Malang Raya, comprises Malang, Batu City and also District ofÂ  Malang, is the city of education, tourism and industry. Sothe development and population growth very rapidly, and to meet the need of inhibitants predicted still need 32000 housing units. This will be followed with the increasing need of the building materials such as wall material fillers. Unfortunately this moment does not effectÂ  significant for enterpreneurs batako making, as the capacity of production and the quality of batako are low and the public is more interested in using brick and batako styrofoam (batafoam). Actually the enterpreneurs batako making can also make batafoam by modifying the sieve and mixer exixting create a new one, and add foam generator equipment, and moldwood or ironplates with 10 holes per units. The differences of batafoam compared with batako are batafoam surface is smoother, the size is 1.5 times larger (10x20x60 cm), the weight is 0.87 times lighter, the production capacity is 1.87 times more.With innovations in the manufacture of hollow brick, then small entrepreneurs can take part in providing wallmaterials fillerand may increase peoples income.